Incidencia de la gamificación en el aprendizaje del área de Ciencias Naturales en 8vo EGB de la Unidad Educativa Fiscomisional "Cacha" - Aguirre Núñez, Andy Marcelo (2024)
The research aims to improve eighth-grade students' participation in the Natural Sciences subject at the Fiscomisional Educational Unit "Cacha" in El Pangui, Ecuador, through gamification to enhance the teaching-learning process. To achieve this goal, specific objectives have been established, which include: conducting a theoretical review of digital proposing a didactic guide that motivates students and enables meaningful learning through gamification. A field study with a mixed approach and a correlational and explanatory design was used. The methods employed were deductive, inductive, and analytical-synthetic, while the techniques included interviews and surveys, using question guides and questionnaires. The sample consisted of eighth-grade students and four teachers from the Fiscomisional Educational Unit "Cacha." The research results indicated that not all students had participated in gamification activities, and very few were familiar with this type of methodology. However, they showed interest in its application for activities and tasks. Likewise, teachers were aware of some interactive applications but did not use them frequently due to a lack of skills. Nevertheless, they believed that implementing these applications during their classes would be a motivating and interesting way to teach. Therefore, an active methodology guide was designed as a promising strategy to make learning more engaging and interactive, helping to achieve the goal of strengthening the educational process and fostering a generation of more committed and curious students. Keywords: Gamification, Teaching and learning, Methodology, Natural Sciences, Didactic guide